APLICACIÓN DE CONTABILIDAD COMERCIAL E INDICADORES FINANCIEROS PARA LA FARMACIA “AUSTRAL” DEL CANTON PIÑAS, PROVINCIA DE EL ORO, PERIODO NOVIEMBRE - DICIEMBRE DE 2015 - Toro Abad, Leidy Patricia (2018)
The present thesis work was carried out with the purpose of contributing with an adequate Accounting Process that the economic situation of the pharmacy, will also serve to comply with the Regulations of Academic Regime that the National University of Loja requires as a prerequisite to choose the Degree of Engineering in Accounting and Auditing, Public Accountant Auditor, CPA During the research process, the proposed objectives were fulfilled, starting with the preparation of the inventory of goods, rights and obligations, followed by the Plan and Manual of Accounts, with the help of the source documents, the accounting record is started until the Obtaining Financial Statements that provide information on the resources it has, the results obtained, the inflows and outflows of cash that it has derived, among other financial aspects. With the obtained results it is concluded that the Application of an Accounting System in the Austral Pharmacy allows to know the yield generated by the invested capital, its Assets, Liabilities and Patrimony obtaining a clear vision of the current financial situation of the business; therefore, its owner is recommended to accept the present proposal in order to adequately control its resources and achieve a prosperous competitive development within the locality.